2018
DOI: 10.4103/sjmms.sjmms_163_16
|View full text |Cite
|
Sign up to set email alerts
|

Management of primary spontaneous pneumothorax: A single-center experience

Abstract: Background:The prevalence of primary spontaneous pneumothorax is high in the Arab region. There is a lack of studies from the Eastern Province of Saudi Arabia highlighting the associated risk factors and demonstrating the effectiveness of surgical management.Objectives:To identify risk factors associated with primary spontaneous pneumothorax and to correlate the effectiveness of surgical management with the rate of disease recurrence.Subjects and Methods:This retrospective chart review included adult patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
3
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
4
3
0
4
Order By: Relevance
“…According to the current guidelines [ 1 , 4 , 5 , 6 ], VATS should be considered at recurrence or in case of persistent air leak after CT treatment. Similar to our results, various studies have proven VATS to be superior to CT treatment in terms of recurrence rates, even at first episode of PSP [ 12 , 13 , 14 ]. VATS has also been reported to be associated with shorter hospitalization rates and better quality of life [ 10 , 11 , 12 , 13 , 16 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…According to the current guidelines [ 1 , 4 , 5 , 6 ], VATS should be considered at recurrence or in case of persistent air leak after CT treatment. Similar to our results, various studies have proven VATS to be superior to CT treatment in terms of recurrence rates, even at first episode of PSP [ 12 , 13 , 14 ]. VATS has also been reported to be associated with shorter hospitalization rates and better quality of life [ 10 , 11 , 12 , 13 , 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…In cases with ipsilateral or contralateral recurrence of PSP and for those with persistent air leak following chest tube (CT) treatment, the guidelines [ 1 , 4 , 5 , 6 ] recommend video-assisted thoracoscopic surgery (VATS). In various studies, VATS bullectomy with or without pleurectomy was associated with very low rates of recurrence and a short length of hospitalization, even at first episode of PSP [ 10 , 11 , 12 , 13 , 14 ]. Therefore, we wondered if preventive surgical intervention might be a suitable alternative to reduce the recurrence rates and associated economic burden, as well as to mitigate the negative psychological impact that results from anxiety about a potential recurrence [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have investigated non-trauma etiologies of pneumothorax in SA. For instance, a study in the Eastern region of the country 12 found that risk factors for primary spontaneous pneumothorax include being male and a smoker; these risk factors are consistent with current literature.…”
supporting
confidence: 83%
“…A bleb é formada em decorrência da rotura de um alvéolo. Com a rotura, o ar alveolar se desloca Já o pneumotórax em sua forma adquirida corresponde ao acúmulo de ar devido a ocorrência de um evento iatrogênico associado aos cuidados de saúde -como punção venosa central, drenagem torácica inadequada, biópsia transtorácica e toracocentese -ao barotrauma ou em decorrência de trauma torácico, seja ele fechado ou penetrante (RODRIGUES, 2019).após o primeiro episódio de pneumotórax espontâneo primário (PSP), em especial em casos com a presença de pneumotórax de grande porte ou um vazamento de ar persistente(ALJEHANI, 2018).Ainda em relação às complicações, os pacientes com trauma torácico podem ter uma morte tardia devido às complicações pleuropulmonares de natureza infecciosa.até sendo superior à radiografia de tórax (RX) em pneumotórax mínimos e localizados. (WONGWAISAYWAN, 2016).…”
unclassified